2022
DOI: 10.2147/pgpm.s359821
|View full text |Cite
|
Sign up to set email alerts
|

Novel Compound Heterozygous Variants in CCDC40 Associated with Primary Ciliary Dyskinesia and Multiple Morphological Abnormalities of the Sperm Flagella

Abstract: Primary ciliary dyskinesia (PCD) is a rare genetic disease caused by mutations of genes coding motile-cilia-related proteins. CCDC40 variants can cause PCD via disrupting the assembling of inner dynein and dynein regulating complex in cilia and flagella, but none has been reported associated with multiple morphological abnormalities of the sperm flagella (MMAF). We identified and validated the disease-causing variants in our patient via whole-exome and Sanger sequencing. We used high-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…They can severely reduce male fertility, but have received less attention in previous PCD studies ( Dávila Garza and Patrizio, 2013 ; Sironen et al, 2020 ). Although >50 PCD-associated pathogenic genes have been reported, a few have been reported to be associated with asthenoteratozoospermia, such as DNAH9 , DNAH1 , ARMC4 , BRWD1 , CCDC39 , CCDC40 , DRC1 , CFAP74 , and SPEF2 ( Neesen et al, 2001 ; Sha et al, 2020 ; Tu et al, 2020 ; Chen et al, 2021 ; Gao et al, 2021 ; Guo et al, 2021 ; Lei et al, 2022 ; Xu et al, 2022 ). In most other cases, researchers have not analyzed the semen of male patients.…”
Section: Discussionmentioning
confidence: 99%
“…They can severely reduce male fertility, but have received less attention in previous PCD studies ( Dávila Garza and Patrizio, 2013 ; Sironen et al, 2020 ). Although >50 PCD-associated pathogenic genes have been reported, a few have been reported to be associated with asthenoteratozoospermia, such as DNAH9 , DNAH1 , ARMC4 , BRWD1 , CCDC39 , CCDC40 , DRC1 , CFAP74 , and SPEF2 ( Neesen et al, 2001 ; Sha et al, 2020 ; Tu et al, 2020 ; Chen et al, 2021 ; Gao et al, 2021 ; Guo et al, 2021 ; Lei et al, 2022 ; Xu et al, 2022 ). In most other cases, researchers have not analyzed the semen of male patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that DRC1 variants could lead to PCD and MMAF, which is the same diagnosis as the patient we reported in this study ( Lei et al, 2022 ). So far, only several genes have been covered to be related to PCD with MMAF, including SPEF2 , CFAP74 , BRWD1 , CCDC39 , CCDC40 , ARMC4 , and DRC1 ( Sha et al, 2020 ; Tu et al, 2020 ; Chen et al, 2021 ; Gao et al, 2021 ; Guo et al, 2021 ; Lei et al, 2022 ; Xu et al, 2022 ). Since the axonemal ultrastructure of respiratory cilia and sperm flagella is highly consistent, it is necessary to consider their sperm motility and morphology when diagnosing a patient with PCD.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal brush biopsy samples were imaged using an upright Olympus BX53 microscope (Olympus, Tokyo, Japan) and recorded using a scientific complementary metal oxide semiconductor camera (Prime BSI, Teledyne Photometrics Inc., United States) as previously described ( Xu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic origin accounts for 35–60% of these MMAF cases. Several gene-families are identified as associated with flagella, including the AKAP family, DANI family, DNAH family, RSPH family, CCDC family, CFAP family, TTC family, and some single genes [ 1 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%